The petitio principii in the formulation of the concept of moral law in the foundation of the metaphysics of customs according to Schopenhauer - Francisco Rodrigues, Eli Vagner [UNESP] (Pontificia Univ Catolica Parana, 2018)
Schopenhauer accuses Kant of having committed a petition of principle in the formulation of the concept of moral law in the Rationale of the Metaphysics of Customs'. The analysis of the concept of moral law is fundamental for Schopenhauer to establish the debt of Kantian ethics in relation to theology, more precisely to the mosaic decalogue. The original meaning of law (lex, nomos), Schopenhauer argues, is limited to civil law, an institution that rests on human agency. A second meaning is the metaphorical sense of nature's law. Both do not apply to moral philosophy. A law in the form of a thou shaltcan not be legitimate by itself. The introduction of the concepts of prescription and duty represent the great flaw of Kant's ethics, the proton pseudo of his moral philosophy, an unacceptable petition of principle that compromises all ethics. Eudemonism, banished as heteronomy, is subtly reintroduced in the form of Sovereign Good. The foundation for the admission of a practical reason would be rational psychology. This doctrine affirmed that the soul would have an upper or lower faculty of knowledge and a faculty of desiring of the same kind. She would be an intellectus purus occupied only with spiritual representations, not sensitive. The pure Kantian reason would then be, according to Schopenhauer, derived from an unconscious reminiscence of this doctrine, the basis of theological considerations. This charge leads Schopenhauer to examine, too, the concept of unconditioned duty, classified as a contradictio in adjecto (contradiction in terms). Schopenhauer concludes that the logical errors committed by Kant were brought about by theological presuppositions.
Keywords: Law; Moral; Duty; Eudemonism; Criticism